The Application of Group Work Method to Increasing Student Learning Activity in the Learning Process - M. Saufi; Darmawanta Sembiring; Muh. Safar; Muhammad Syahrul; Augusta De Jesus Magalhaes (Journal on Education, 2023)
The purpose of this study is to analyze how using group work techniques has increased student learning activity. Class action research is the approach employed in this study. Planning, carrying out, observing, and reflecting are the four stages of this process. This study was carried out between March and May with participants in classes V. The study was done over the course of two cycles, with two meetings per cycle. The findings indicated that student learning activity increased with each cycle. This is demonstrated by the results of the students that participated in cycle I, where five students achieved a percentage of 15.62% and an average student learning activity of 62.19%. As opposed to cycle II, where 28 (twenty eight) students were active, the average student learning activity was 88.92% and the percentage of active students was 87.50%. In light of the average percentage of active students meeting the desired action intervention results, i.e. 80%, it can be stated that the implementation of the group work approach can boost the activeness of student learning. Increased student learning activity was accompanied by successful learning outcomes, namely 83.